Long-term Follow-up of Pulmonary Function and Scoliosis in Patients With Duchenne's Muscular Dystrophy and Spinal Muscular Atrophy - Chua, Kenon (LIPPINCOTT WILLIAMS & WILKINS, 2023)
10.1097/BPO.0000000000000396